DIREITO E ECONOMIA ÀS VESTES DO CONSTITUCIONALISMO GARANTISTA - Neto, Alfredo Copetti; Schorr, Janaína Soares; Garcia, Mariana da Silva; Marcht, Laura Mallmann; Bronzatti, Bruna Fernanda (Salão do Conhecimento, 2015)
Resumo